ПРАВОПИСОТ НА МАКЕДОНСКИОТ СТАНДАРДЕН ЈАЗИК ВО ПРАКТИЧНА УПОТРЕБА (Philological Studies, 2019)
The paper indicates the inconsistencies in the usage of the slash in the written form regarding the standard language norm. Through analysis of extensive literature, examples of those inconsistencies are shown which simultaneously entail the need for more thorough standardisation and revision of certain orthographic solutions established within the codification in regards to punctuation and orthographic marks, and the inclusion of the slash into categories of the already existing punctuation and orthographic marks.
Keywords: orthography, usage, slash